Rate of neonatal birth HIV positive tests and description of related risk factors in Johannesburg: can point of care testing be targeted effectively? - Wannenburg, Elzette (My University, 2024)
Background Prompt diagnosis of Human Immunodeficiency Virus (HIV) in South Africa and early initiation of antiretroviral therapy in infected newborns remains a challenge in South Africa. Point of Care Testing could expedite this process. This study describes the rate of, and risk factors associated with birth detectable HIV infection in a South African setting. Methods A secondary data analysis of infant HIV polymerase chain (PCR) reaction results was done at Rahima Moosa Mother and Child Hospital in Johannesburg between June 2014 to June 2019. Annual positivity rates were calculated and association tested against characteristics (maternal, delivery and infant) using descriptive statistical methods. Results 12466 infants had a final HIV result. The yearly positivity rate did not show significant fluctuation, ranging from 1.2-1.7%. Maternal risk factors for infant infection included adolescent age (3.6% vs 1.8% for mothers aged 20-30) (p1000 (8.9% vs 1.3% if 50-1000) (p<0.001); CD4 count <200 (3.3% vs 0.75% at CD4 200- 300) (p<0.001); antiretroviral therapy for less than a month (5.1% vs 2.3% after 1 month) (p<0.001); HIV diagnosis within a month of delivery (10.1% vs 1% preconception) (p<0.001) and those with viral loads >1000 (8.9% vs 1.3% if 50-1000) (p<0.001). Infant risk factors for infection were prematurity (2.3% vs 1.4%) (p=0.012); low birth weight (2.2% vs 1.4%) (p=0.009); ill infants warranting admission (3% vs 1.5%) (p<0.001) and infants born in cold seasons (1.8 vs 1.3%) (p=0.016). Conclusion Various maternal and infant factors were associated with HIV infection at birth while the birth positivity rate remained relatively constant across the study period. While universal birth point of care testing is ideal, high risk infant groups could be identified and targeted in resource constrained settings to expedite HIV diagnosis and treatment
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: HIV positive tests; Neonatal birth; SDG-3: Good health and well-being